A Critique of John Wansbrough's Methodology and Conclusions - Mohammad Nasir, Mohammad Nasrin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Critique of John Wansbrough's Methodology and Conclusions